Histopathological effects on epidural tissue of bolus or continuous infusions through an epidural catheter in ewes - (:unkn) unknown (WILEY-BLACKWELL, 2010)
P>This study was performed to evaluate the histopathological effects of epidural drug injection given either by intermittent bolus or continuous infusion through a catheter on epidural tissue. Fourteen ewes received intermittent bolus injections of morphine with bupivacaine, or a bolus of the same drugs followed by continuous infusion for 5 days. After 5 days, histopathological examination of the epidural space revealed mild to moderate inflammatory changes, and focal fibrosis surrounding the catheter in all ewes. The similarity of the inflammatory reaction in the control and drug treated groups seems to indicate that neither intermittent bolus or continuous infusion after a bolus dose caused histopathological changes in the epidural space beyond that caused by the catheter itself.
Keywords: BUPIVACAINE; MORPHINE; SHEEP; NEUROTOXICITY; RABBITS; MODEL; RATS; ROPIVACAINE; INJECTIONS; LIDOCAINE